COVID-19 workplace countermeasures that occupational physicians could not change in Japan: a qualitative study - Yu Igarashi; Seiichiro Tateishi; Juri Matsuoka; Tomoko Sawajima; Mika Kawasumi; Arisa Harada; Koji Mori (BMC Public Health)
Abstract Background During the COVID-19 pandemic, information and circumstances changed from moment to moment, including the accumulation of scientific knowledge, the emergence of variants, social tolerance, and government policy. Therefore, it was important to adapt workplace countermeasures punctually and flexibly based on scientific evidence and according to circumstances. However, there has been no assessment of changes in workplace countermeasures. With a view toward preparedness for future pandemics, we surveyed COVID-19 workplace countermeasures that occupational physicians considered as needing to be changed but went unchanged. Methods We invited 685 professional occupational physicians certified by Japan Society for Occupational Health to complete an online questionnaire by sending postcards with QR codes. The main questions concerned countermeasures that the participants wanted to change but could not. The survey period was from February 21 to April 28, 2022. The responses were analyzed using the KJ method. Results Of the 168 invitees (24.5%) who responded to the survey, 125 reported countermeasures that needed to be changed (total count: 254). The responses were categorized into basic systems, occupational health services, workplace countermeasures, vaccines, and incidents, with a code count of 7, 8,147, 10, and 82, respectively. The type of countermeasure was 115 for countermeasures to be strengthened (CBS), 110 for measures to be mitigated (CBM), and 29 for neither. Conclusions Often-mentioned CBS were increased teleworking, strengthened ventilation, smoking cessation, and promotion of vaccines. Often-mentioned CBM were relaxation of protective equipment rules, discontinued environmental disinfection, and shorted isolation and reinstatement. In the early pandemic phases, CBSs were frequently mentioned, whereas CBMs were featured more prominently in the latter phases. The survey revealed countermeasures that occupational physicians thought needed to be changed but were not changed in practice. For future responses to emerging and reemerging infectious diseases, it will be necessary to establish rules compatible with flexible modification of workplace countermeasures in response to changing circumstances.